Family Policymaking in the US and UK from 1960 to 2010: A Comparative Analysis of Civil Society and Legal Frameworks from a Feminist Perspective - (:unkn) unknown (My University, 2013)
Why do countries have different family policy outcomes? This comparative analysis of maternity, paternity and family leave policies in the United States and United Kingdom traces the historical development of family policies from 1960-2010 in order to understand the trajectory of the gendered welfare state. The dissertation uncovers the impact that the social construction of gender has on family policy outcomes. I look to civil society activity and the legal framework for evidence of gender norms. Analysis draws on field research, interviews, archival sources and data collected from governmental and nongovernmental organizations. I suggest that the social construction of gender influences policymaking and helps to explain the path dependent development of family policies over time. With contrasting equality frameworks in each country established in the mid-1960s, I find that the policy trajectories are largely unchanged. Thus, there are limited opportunities for significantly altering the future development of family policies.
Keywords: Civil Society; Family Leave; Maternity Leave; Path Dependency; Social Construction of Gender; Welfare State